Telehealth for patients at high risk of cardiovascular disease: pragmatic randomised controlled trial. - Salisbury, C; O'Cathain, A; Thomas, C; Edwards, L; Gaunt, D; Dixon, P; Hollinghurst, S; Nicholl, J; Large, S; Yardley, L; Fahey, T; Foster, A; et al. (BMJ Publishing Group, 2016)
Objectives To assess whether non-clinical staff can effectively manage people at high risk of cardiovascular disease using digital health technologies. Design Pragmatic, multi-centre, randomised controlled trial. Setting Participants recruited from 42 general practices in three areas of England Participants Between 3 December 2012 and 23 July 2013 we recruited 641 adults aged 40 to 74 years with 10 year cardiovascular disease risk ≥20%, no previous cardiovascular event, at least one modifiable risk factor (systolic BP ≥140; body mass index ≥30; current smoker) and access to telephone, internet and email. Interventions Participants individually allocated to intervention (n= 325) or control (n= 316) using automated randomisation stratified by site, minimised by practice and baseline risk score. Intervention: The Healthlines Service (alongside usual care), comprising regular telephone calls from trained lay health advisors following scripts generated by interactive software. Advisors facilitated self-management by supporting participants to use online resources to reduce risk factors and sought to optimise medication, improve treatment adherence and encourage healthier lifestyles. Control: usual care alone. Main Outcome Measures Primary outcome: proportion of participants responding to treatment, defined as maintaining or reducing their cardiovascular risk after 12 months. Outcomes were collected 6 and 12 months after randomisation and analysed masked. Participants were not masked. Results 50.2% (148/295) of intervention group participants responded to treatment compared with 42.6% (124/291) in the control group (adjusted odds ratio 1.3; 95% confidence interval 1.0 to 1.9; number needed to treat = 13); a difference possibly due to chance (p=0.079). The intervention was associated with reductions in BP (difference in mean systolic -2.7 mmHg (-4.7 to -0.6), mean diastolic -2.8 (-4.0 to -1.6)); weight (-1.0 kg (-1.8 to -0.3)), and body mass index (-0.4 (-0.6 to -0.1)) but not cholesterol (-0.1 (-0.2 to 0.0), smoking status (adjusted OR 0.4 (0.2 to 1.0)), or overall cardiovascular risk as a continuous measure (-0.4 (-1.2 to 0.3)). The intervention was associated with improvements in diet, physical activity, medication adherence, and satisfaction with access to care, treatment received and care co-ordination. There was one serious related adverse event: a participant hospitalised with low BP. Conclusionss This evidence based telehealth approach was associated with small clinical benefits for a minority of people with high cardiovascular risk, and there was no overall improvement in average risk. However, the Healthlines Service was associated with improvements in some risk behaviours, and in perceptions of support and access to care.